Synthesis and optical properties of lead-free cesium germanium halide perovskite quantum rods. Issue 33 (21st May 2018) - Chen, Lin-Jer
Abstract : Herein, the fabrication of a lead-free cesium germanium halide perovskite produced via a simple solvothermal process is reported for the first time. Abstract : Herein, the fabrication of a lead-free cesium germanium halide perovskite produced via a simple solvothermal process is reported for the first time. By tuning the composition of the CsGeX3 quantum rods, a power conversion efficiency of 4.92% under AM 1.5 G was achieved.